1991
DOI: 10.1111/j.1365-2427.1991.tb01401.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus retention in streams draining pine and hardwood catchments in the southern Appalachian Mountains

Abstract: 1. This study was designed to determine how catchment use affects stream phosphorus retention by comparing retention in streams draining three mixed hardwood catchments and three catchments that were planted in white pine in the 1950s.2. Catchments of similar area and stream discharge were chosen and phosphorus uptake was measured monthly in each catchment along with temperature, discharge, velocity, coarse particulate organic matter (CPOM), fine particulate organic matter (FPOM), and microbial respiration ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 26 publications
4
17
0
Order By: Relevance
“…Variations in S w within or among seasons are often the result of variation in discharge (Butturini and Sabater, 1998), and several investigations have found positive relations between S w and velocity and/or discharge (see D'Angelo and Webster, 1991;Martí and Sabater, 1996;Valett et al, 1996). Similar to these existing reports, S w -SRP was shortest when discharge was lowest at all sites, and it became longer at higher discharges ( fig.…”
Section: Nitrate-n Concentrations Increased Downstream In Drysupporting
confidence: 76%
See 1 more Smart Citation
“…Variations in S w within or among seasons are often the result of variation in discharge (Butturini and Sabater, 1998), and several investigations have found positive relations between S w and velocity and/or discharge (see D'Angelo and Webster, 1991;Martí and Sabater, 1996;Valett et al, 1996). Similar to these existing reports, S w -SRP was shortest when discharge was lowest at all sites, and it became longer at higher discharges ( fig.…”
Section: Nitrate-n Concentrations Increased Downstream In Drysupporting
confidence: 76%
“…Several studies have shown spatial variation in S w within and among streams (Aumen et al, 1990;D'Angelo and Webster, 1991;Martí and Sabater, 1996;Munn and Meyer, 1990), and others have examined temporal variation in S w (Martí and Sabater, 1996;Mulholland et al, 1985;Webster et al, 1991). Spatial variation may result from differences in channel form, local environmental conditions, watershed land use, and physiographic features, whereas temporal variation is largely related to temperature, hydrology, and allochthonous inputs into the stream ecosystem.…”
mentioning
confidence: 99%
“…Dissolved inorganic P is considered bioavailable, whereas organic and particulate P forms generally must undergo transformations to inorganic forms before being considered bioavailable. Other researchers have proposed three size fractions of P: dissolved (DP, < 0.45 µ m), fine particulate (FPP, 0.45 µ m to 1 mm), and course particulate (CPP > 1 mm) (D'Angelo and Webster, 1991) to help define sedimentation, transportability, and reactivity. However, these size fractions of P are not necessarily indicative of P bioavailability or chemistry.…”
Section: Phosphorus Retention Mechanismsmentioning
confidence: 99%
“…Usually the majority of spiraling length is uptake length, the average distance a nutrient atom travels in dissolved inorganic form before it is immobilized by either biotic or abiotic processes (Ball and Hooper 1963;Stream Solute Workshop 1990;Newbold 1992). In addition to extensive use in studies of relatively undisturbed streams (e.g., Webster et al 2003), nutrient uptake length has been used to measure stream response to forest and riparian management D'Angelo and Webster 1991;Sabater et al 2000;Valett et al 2002), waste water treatment plant effluent (Haggard et al 2001), and dam removal (Doyle et al 2003 Ball and Hooper (1963). Elwood and others used radioactive phosphorus as a tracer to measure uptake of phosphorus in Walker Branch, TN (Elwood and Nelson 1972;Newbold et al 1983;Mulholland et al 1985), and similar studies of phosphorus have been conducted at a few other sites (e.g., Gregory 1978;Hart et al 1991;Mulholland et al1997).…”
mentioning
confidence: 99%